Postpartum lifestyle behaviour among women with prior gestational diabetes mellitus: evidence from the HUNT study - Vegar Rangul; Julie Horn; Hanne Ringvoll; Marit Kolberg; Ingrid Hafskjold; Eirin Beate Haug; Rune Blomhoff; Hege Berg Henriksen (BMJ Nutrition, Prevention & Health)
Introduction Women with a history of gestational diabetes mellitus (GDM) are at increased risk of type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Recommendations for postpartum follow-up include targeted lifestyle advice to lower the risk.The aim of this study was to compare postpartum lifestyle behaviours and perceptions among women with and without a history of GDM. In addition, we examined whether lifestyle behaviours of women with a history of GDM participating in a lifestyle intervention study differed from lifestyle behaviours of women with a history of GDM in the general population.Research design and methods We linked data from the fourth survey of the population-based Trøndelag Health Study (HUNT4) to information from the Medical Birth Registry of Norway for women with registered births between 2000 and 2019. Using logistic regression, we compared lifestyle behaviours in women with and without GDM. In secondary analyses, lifestyle behaviours in women with GDM participating in a postpartum lifestyle intervention study were compared with HUNT participants with GDM using Fisher’s exact tests/t-tests.Results A high proportion of the women in our population, regardless of GDM history, reported several unhealthy lifestyle behaviours. We found no significant association between history of GDM and lifestyle behaviours. The lifestyle intervention study for women with a history of GDM appeared to recruit women with more favourable lifestyle behaviours.Conclusions Women, regardless of GDM history, could potentially benefit from further support for lifestyle improvement, but it may be especially important in women with a history of GDM given their increased risk of T2DM and CVD. Interventions targeting women with GDM might not reach the women with the unhealthiest lifestyle behaviours, and measures to reach out to all women should be further investigated.